2013
DOI: 10.1111/ejss.12103
|View full text |Cite
|
Sign up to set email alerts
|

Transient biochar effects on decomposer microbial growth rates: evidence from two agricultural case‐studies

Abstract: Summary We investigated the impact of biochar application on fungal (acetate incorporation into ergosterol) and bacterial (leucine incorporation) growth rates in two case studies: a temperate UK pasture soil and a Mediterranean Australian agricultural soil. We added biochar at similar rates per unit of soil organic carbon (SOC) and monitored both the immediate (after 1 week equilibration) and longer‐term (1–3 years) effects. The immediate effect of the biochar applied to the UK soil was a decreased fungal‐to‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Our null result is likely linked to the fact that there was no overall effect of adding biochar at 5 t ha −1 on soil pH, as discussed previously. Changes in microbial community composition after biochar addition are often correlated with pH (Rousk et al 2013;Anders et al 2013), and in the present study, soil pH was the main control on the fungi/bacteria ratio in the organic layer and pH was also correlated with bacterial community composition in 2012. There was also a significant decrease in the fungi/bacteria ratio in the organic layer of the maple biochar plots, which may have been linked to pH changes.…”
Section: Microbial Community Compositionsupporting
confidence: 61%
See 4 more Smart Citations
“…Our null result is likely linked to the fact that there was no overall effect of adding biochar at 5 t ha −1 on soil pH, as discussed previously. Changes in microbial community composition after biochar addition are often correlated with pH (Rousk et al 2013;Anders et al 2013), and in the present study, soil pH was the main control on the fungi/bacteria ratio in the organic layer and pH was also correlated with bacterial community composition in 2012. There was also a significant decrease in the fungi/bacteria ratio in the organic layer of the maple biochar plots, which may have been linked to pH changes.…”
Section: Microbial Community Compositionsupporting
confidence: 61%
“…Soil nutrient availability was not measured in 2013, but Sackett et al (2014 found that most nutrient effects observed within 2 to 6 weeks after biochar addition were no longer present by the end of the first year (other than increased Ca 2+ levels), suggesting that many nutrient effects at this site were transient. Similarly, the resiliency of the microbial community should likewise result in only transient effects of biochar additions (Quilliam et al 2012;Rousk et al 2013). In this study, we found effects on the mineral soil microbial community composition, but not in the organic soil layer, in the second year after biochar addition.…”
Section: Microbial Community Compositionmentioning
confidence: 47%
See 3 more Smart Citations